Policing the Seas : Anglo-American Relations and the Equatorial Atlantic, 1819-1865. - Hunter, Mark C. (Research in Maritime History LUP., 2017)
This study explores the British and American attempts to suppress both piracy and slavery in the equatorial Atlantic in the period 1816 to 1865.